Gambaran Tingkat Pengetahuan Lansia Tentang Gout Arthritis di Desa Pinabetengan Utara Kecamatan Tompaso Barat Kabupaten Minahasa - Grace Merentek; Linnie Pondaag; Pingkan Christy Timbuleng; Emsjun Kurnia Frisilia Pantow (Yayasan Syalom Cipta Sumikolah, 2024)
As we age, the body becomes increasingly susceptible to health problems due to decreased function of the body's organs. There are several health problems that commonly occur in the elderly, including hypertension, diabetes mellitus, stroke, chronic obstructive pulmonary disease (COPD), depression and gouty arthritis. The presence of gouty arthritis in the elderly often reduces their quality of life. Therefore, it is important for us to understand this disease, recognize its symptoms, and know how to prevent it. In this way, we can provide support to the elderly to live more comfortably even with gouty arthritis. This research aims to determine the description of knowledge of elderly people about gouthy arthritis in North Pinabetengan Village, West Tompaso District, Minahasa Regency. This type of research is descriptive research. The samples in this study were some elderly people in North Pinabetengan Village, West Tompaso District, Minahasa Regency. The results of the research show that the level of knowledge of elderly people about Gouthy is good. It is recommended that the elderly continue to maintain and improve their knowledge about Gouty Arthritis so that the quality of life of the elderly is more productive.